Duch - Master of the Forges of Hell - Rithy Panh; Prum Mésar
Between 1975 and 1979, the Khmer Rouge was responsible for the death of nearly 2 million people - a quarter of the Cambodia population. Kaing Guek Eav, known as Duch, directed both the M13 and S21 centers where tens of thousands of people were tortured and executed. He also is the first Khmer Rouge leader to be brought before an international criminal justice court; he was found guilty and sentenced to 35 years in prison. Panh films an incredible, horrifying in-depth interview with Duch, who candidly talks about his ascension in the Khmer Rouge party, and his involvement in the mass murder of his fellow Cambodians. As "The Hollywood Reporter" said, Panh's film is "likely one of the most elaborate discussions with someone responsible for mass genocide." [www.amazon.com]